Organizational behavior and management in family businesses - Yazici, Ömer (Cambridge Scholars Publishing, 2022)
Family firms constitute more than 80% of businesses and employ 60% of the workforce worldwide. This book presents valuable insights about how these firms operate and how their employees feel. It explores HR management issues, family integration as a source of competitive advantage, the financial management practices of family firms. In addition to offering a comprehensive analysis of managerial issues in family businesses, it also provides state of the art findings about these challenges.